A critical assessment of the South African bond market - Sze, Winnie W Y (Research of GSB, 2018)
This paper looks at the experience of South Africa in the development of its local‐currency, so‐called domestic, bond market. Whilst South Africa had the deepest financial market in Sub‐Saharan Africa it also had one of the shallowest domestic bond markets, until 2009. This changed with the rapid bond issuances by the national government as a means to fund its expanding government expenditure. The paper finds that the government issuances served to deepen the market for rand‐based bonds and lengthen the maturities of bonds, for the benefit of itself, state‐owned enterprises, and the private sector, particularly the banks. At the same time, it has heightened the risk of negatively impacting economic development. The World Bank and other multilaterals advocate the development of the domestic bond market as a financial cushion against financial stress and as a way to better channel domestic savings towards domestic investment. There is argument that South Africa's domestic bond market acts as a substitute and competition for the dominant bank market. At the same time, given the market infrastructure and regulation, there is also high risk that the bond market could act as a co‐contagion in the event of a bank crisis. There is no evidence that total savings improved as a result of the bond market, however the provision of a long‐term instrument more theoretically suitable to South Africa's specialist pension and insurance funds suggest that the market provides beneficial intermediation. The recommendations focus on mitigating the negative biases of market infrastructure supports and the pension fund regulation.